Ecological parameters and biotic damage pattern in invasive alien species across land-use types in Kathmandu, Nepal - Deuba, Reetu; Thapa, Lal B.; Kaewchumnong, Krittika; Jha, Sanjay Kumar (Botanica Orientalis: Journal of Plant Science, 2025)
Invasive alien plant species (IAPS) are responsible for severe damage to ecosystems, causing huge economic loss. It has been considered that the IAPS are comparatively less damaged by herbivores and pathogens in the invaded range. This study assessed the effects of herbivore and pathogen damage (biotic damage) on the common IAPS, Ageratina adenophora, Ageratum conyzoides, Bidens pilosa, and Parthenium hysterophorus in the Chobhar area of Kathmandu, Nepal. Additionally, the density, frequency, and coverage of these IAPS were compared across different land-use types, such as fallow land, forest, and roadside, along the northern and southern aspects. A negative relationship was observed between B. pilosa and A. adenophora, as well as P. hysterophorus, suggesting competition for light resources, where one species reduced the cover of the other. Biotic damage differed across land-use types, with B. pilosa experiencing less damage in forest and P. hysterophorus more damage along road verges, indicating habitat-specific activities of herbivores and pathogens.